FATAL ELECTROCUTION : THREE YEARS RETROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2016)
Background & objectives: Electricity is an integral part of human life in modern time and it is hard to imagine life without it. But with advantages and convenience electricity is also responsible for considerable morbidity and mortality which are preventable with simple safety measures. This study was undertaken in an effort to evaluate the Epidemiological & Medico Legal aspects of electrocuted deaths to precisely understand the dynamics of these deaths. Methods: Present study was observational retrospective study on fatal cases of electrocution excluding lightening brought for Medico Legal autopsy at Dept. of Forensic Medicine, Govt. Medical College, Bhavnagar from 1st Jan 2009 to 31st Dec-2011. Results: Most of the deaths were accidental with male predominance. Most of the deaths occured in domestic surrounding and predominating age group of 11-50 Years.Most of the cases observed in rainy season.Most of the deaths were preventable with easy safety measures.
Keywords: Electrocution,; Accidental Deaths; Gujarat; India